Are therapeutic motivation and having one's own doctor as researcher sources of therapeutic misconception?. Issue 5 (22nd May 2014) - Kim, Scott Y H; De Vries, Raymond; Parnami, Sonali; Wilson, Renee; Kim, H Myra; Frank, Samuel; Holloway, Robert G; Kieburtz, Karl
Abstract : Background: Desire for improvement in one's illness and having one's own doctor functioning as a researcher are thought to promote therapeutic misconception (TM), a phenomenon in which research subjects are said to conflate research with treatment. Purpose: To examine whether subjects' therapeutic motivation and own doctor functioning as researcher are associated with TM. Methods: We interviewed 90 persons with advanced Parkinson's disease (PD) enrolled or intending to enrol in sham surgery controlled neurosurgical trials, using qualitative interviews. Subjects were compared by motivation (primarily therapeutic vs primarily altruistic or dually motivated by altruistic and therapeutic motivation), and by doctor status (own doctor as site investigator vs not) on the following: understanding of purpose of study; understanding of research procedures; perception of chance of direct benefit; and recollection and perceptions concerning the risks. Results: 60% had primarily therapeutic motivation and 44% had their own doctor as the site investigator, but neither were generally associated with increased TM responses. Overall level of understanding of purpose and procedures of research were high. Subjects responded with generally high estimates of probability of direct benefit, but their rationales were personal and complex. The therapeutic-motivation group was more sensitive to risks. Five (5.6%) subjects provided incorrect answers to the question about purpose of research, and yet, showed excellent understanding of research procedures. Conclusions: In persons with PD involved in sham surgery clinical trials, being primarily motivated by desire for direct benefit to one's illness or having one's own doctor as the site investigator were not associated with greater TM responses.